2021
DOI: 10.4103/jips.jips_295_20
|View full text |Cite
|
Sign up to set email alerts
|

Management of perishing implants with abutment screw fracture – A systematic review

Abstract: Aim: To systematically review the reported techniques, for evaluating the risk and difficulty encountered in the management of fractured abutment screw in accordance with the location of fracture, and to develop a logical sequence in managing an implant abutment screw fracture. Settings and Design: Systematic review following PRISMA guidelines. Materials and Methods: A systematic search of the PubMed/MEDLINE database for articles published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…By taking these factors into account, clinicians can proactively address the issue of screw loosening in implant-supported restorations, ultimately enhancing the longevity and stability of the treatment [ 35 ]. The etiology of screw fractures is multifactorial and can include factors such as inadequate treatment planning, misfit of components, inadequate screw tightening, excessive loading, and inadequate screw design [ 36 ]. Inadequate treatment design and planning can stem from patient assessment and insufficient number and positioning of implants.…”
Section: Discussionmentioning
confidence: 99%
“…By taking these factors into account, clinicians can proactively address the issue of screw loosening in implant-supported restorations, ultimately enhancing the longevity and stability of the treatment [ 35 ]. The etiology of screw fractures is multifactorial and can include factors such as inadequate treatment planning, misfit of components, inadequate screw tightening, excessive loading, and inadequate screw design [ 36 ]. Inadequate treatment design and planning can stem from patient assessment and insufficient number and positioning of implants.…”
Section: Discussionmentioning
confidence: 99%
“…The initial step in the management of fractured screws is to obtain a detailed history and perform a thorough clinical examination. Raju et al systematically reviewed the management of fractured abutment screws to develop a logical sequence for management [ 18 ]. They reported that the harm to implants resulting from the removal of abutment screw fragments ranges from mild to severe regardless of the technique used.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…A retrieval kit may also be used. A hole can be made in the fractured screw to unwind it by engaging a drill [ 18 ]. Abutment screws modified with a prefabricated access hole are easier to retrieve [ 19 ].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies[ 7 8 9 18 24 25 ] to explain the causes of screw loosening, but none of them are conclusive. Almost all agree that loosening will not happen until the friction force between the threads is reduced by some external mechanism.…”
Section: Discussionmentioning
confidence: 99%